2018
DOI: 10.18203/2320-1770.ijrcog20180872
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of pregnancy associated asymptomatic bacteriuria in a tertiary care hospital

Abstract: Background: Urinary tract infections are a common occurrence in pregnancy. The physiological and anatomical changes associated with pregnancy predispose to UTIs. Main aim of the study is to determine the prevalence of asymptomatic bacteriuria in pregnant women, to identify the commonest microorganisms and antibacterial susceptibility of the isolated organism and to study the adverse maternal and fetal outcome.Methods: Prospective cross sectional study, conducted between July 2016 to July 2017 in a tertiary hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…ASB was more prevalent in women of low socioeconomic class (68%) although not statically significant. These findings are similar to those obtained by (Kerure et al, 2012;Bose and Revankar, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…ASB was more prevalent in women of low socioeconomic class (68%) although not statically significant. These findings are similar to those obtained by (Kerure et al, 2012;Bose and Revankar, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…The antibiotic susceptibility patterns of Gram Negative bacteria showed that meropenem, azreonam and nitrofurantoin were effective in more than half of these isolates. These findings are in agreement with an Indian study (Bose and Revankar, 2018) stated that meropenem was the most sensitive antibiotic (84%), followed by cefaperazone (73.1%) and nitrofurantoin (69.2%). The antibiotic with the overall highest sensitivity pattern in this study was meropenem, however, nitrofurantoin showed an appreciated sensitivity rates in Proteus, morganella, E coli and CoNs, these findings are quite similar to those obtained by (Onoh et al, 2013), so nitrofurantoin could be a good option in the management of UTI in pregnancy, especially when the isolated organism has good sensitivity to nitrofurantoin.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations